Prenatal caffeine exposure modifies development and reflexes of neonates and anxiety of young adult mice - Jamaan , S. Ajarem; Mohammad Ahmad (Universiti Kebangsaan Malaysia, 1996)
The effects of prenatal caffeine exposure were examined on the morphological development and early development of reflexes in the mice pups, and further, the anxiety was also studied in the weaned mice using the plus-maze test. It was found that the postnatal body weight gain of the treated pups declined significantly. The normal eye-opening and hair appearance were also affected in the pups due to caffeine treatment. Measurement of early development of sensory motor reflexes in the pups showed that during the first week, caffeine had significantly stimulated the righting reflex, cliff avoidance and rotating reflexes with interaction between age and treatment doses. It was found in the plus-maze test that caffeine had significantly reduced the percentages of time spent as well as the entries into the open arms indicating for an anxiogenic action of caffeine in the young adult mouse. Also, caffeine stimulated the locomotor activity in the mouse as exemplified by an increase in the total number of arm entries in the plusmaze task. The present data support the basic conclusion that prenatal caffeine has a direct in utero action on the reflexes of the developing mouse pups and the anxiogenic action produced in them is longer lasting in nature.